The golden age of disaster cinema : a guide to the films, 1950-1979 - Havert, Nik, 1970- (McFarland & Company, Inc., 2019)
"From the 1950s through the 1970s, disaster films were among the most popular of any genre. This book is a guide to disaster films of this golden age. Featuring interviews as well as vintage photos, lobby cards, and production stills, The Golden Age of Disaster Films a fascinating look into the genre of disaster cinema"--